PENGUATAN BRAND EQUITY MELALUI ANALISIS SWOT PADA STRATEGI RETAIL MIX INDOMARET GADING SERPONG: KONTRIBUSI SDG’S - Kurniadjaya, Morgan; Setiyowati, Harlis (Gapenas Publisher, 2024)
This study examines the enhancement of brand equity through SWOT analysis within the retail mix strategy of Indomaret Gading Serpong, with a focus on contributing to the Sustainable Development Goals (SDGs). Brand equity, a critical asset for any business, represents the value and perception consumers hold towards a brand. In a competitive area like Gading Serpong, strengthening brand equity is vital for sustaining market presence. This research utilizes SWOT analysis to identify Indomaret’s internal strengths and weaknesses, as well as external opportunities and threats. The study explores how Indomaret can leverage its strengths, address its weaknesses, capitalize on opportunities, and mitigate threats to enhance its brand equity. Additionally, the research aligns these strategies with SDGs, particularly SDG 1 (No Poverty) and SDG 8 (Decent Work and Economic Growth), demonstrating Indomaret’s potential to contribute positively to local economic development and poverty reduction. The findings suggest that by adopting a comprehensive retail mix strategyencompassing product innovation, quality service, effective marketing, and sustainability initiatives Indomaret can improve its competitive advantage and brand equity. This approach not only enhances business performance but also supports broader socio-economic goals, providing a model for other retailers aiming to achieve sustainable growth